The Marine Radiocarbon Reservoir Effect on Adak Island (Central Aleutian Islands), Alaska. Issue 5 (2015) - Khasanov, Bulat F; Nakamura, Toshio; Okuno, Mitsuru; Gorlova, Ekaterina N; Krylovich, Olga A; West, Dixie L; Hatfield, Virginia; Savinetsky, Arkady B
Abstract : Radiocarbon dates ( n = 18) from three archaeological sites on Adak Island, Alaska, were analyzed to understand the marine reservoir offset. Samples of marine and terrestrial origins recovered from the same archaeological context were compiled in nine pairs. The mean ΔR value calculated for them totaled 545 ± 10 yr. This value can be regarded as a sound estimate of the marine reservoir offset in the central Aleutians.